Festival of Britain, 1951 (London, 1951)
1951 1945-1951 "Festival of Britain, 1951" [BW0182], 1951, Trades Union Congress The Festival of Britain was an attempt to give the post-war period a feeling of recovery and progress and to promote better-quality design in the rebuilding of British towns and cities following the war. The Labour Party's Deputy Leader, Herbert Morrison, described it as "a tonic for the nation". This photograph of workers in the steel industry is from the Labour Party pamphlet 'Festival', published in June 1951.